Being Mother: Comparative Study of the Contested Motherhood between South Korea and Indonesia - Desintha Asriani (Research Synergy Foundation, 2017)
This paper attempts to explain the discourse of motherhood in both South Korea and Indonesia. It is based on the interesting dynamic of being mother that is much influenced by the interrelated actions played by number of dominant actors around woman itself. By using a comparative study, it is found that the map or the trace of political economy in terms of developmental agenda, in fact drives the difference flows in shaping the notion of motherhood. In Indonesia, for being mother, women exist in the intersection of state intention, industrialization and culture pressure. Indonesian motherhood is interestingly in line with another analysis, such in their relation with housemaids. Meanwhile, in South Korea, the description of motherhood occurs in the middle of nationalism spirit, competition, ambience and family routine. Hence, this study concludes that being mother is highly contested and closely associated with the endless structural and cultural issues.